2014
DOI: 10.3109/19401736.2014.883611
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of sugar beet (Beta vulgarisssp.vulgaris)

Abstract: The complete nucleotide sequence of the sugar beet (Beta vulgaris ssp. vulgaris) chloroplast genome (cpDNA) was determined in this study. The cpDNA was 149,637 bp in length, containing a pair of 24,439 bp inverted repeat regions (IR), which were separated by small and large single copy regions (SSC and LSC) of 17,701 and 83,057 bp, respectively. 53.4% of the sugar beet cpDNA consisted of gene coding regions (protein coding and RNA genes). The gene content and relative positions of 113 individual genes (79 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…vulgaris ) (Li et al, 2014). The size of the S. oleracea cp genome (150,725 bp) (Schmitz-Linneweber et al, 2001) is intermediate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…vulgaris ) (Li et al, 2014). The size of the S. oleracea cp genome (150,725 bp) (Schmitz-Linneweber et al, 2001) is intermediate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…vulgaris (GenBank accession number KJ081864.1, Beta vulgaris subsp. vulgaris ) (Li et al, 2014), two closely related species in the Amaranthaceae family, were downloaded from GenBank databases (www.ncbi.nlm.nih.gov). These were used for comparison with the complete cp genomes of HA and HP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed a typical quadripartite structure similar to that of the cp genomes of most land plants (Li et al, 2014;Wang et al, 2013), with large and small single copy regions (LSC and SSC) separated by two copies of inverted repeats (IRa and IRb). The entire gene contents and relative positions of 131 individual genes (86 PCGs, eight rRNA, and 37 tRNA genes) were identical between the two C. sativa cp genomes.…”
mentioning
confidence: 93%
“…With the accumulation of angiosperm cp genomes, comparative genomics and phylogenomics of closely related cp genomes are very useful for grasping the genome evolution regarding structure variations, nucleotide substitutions, and gene losses (Hu et al, 2017;Raman et al, 2016;Barrett et al, 2016). Meanwhile, lots of high-resolution genetic markers, such as intergenic spacer (IGS) fragments , simple sequence repeats (SSRs) , single nucleotide polymorphisms (SNPs) (Li et al, 2014), and repeated sequences (Provan et al, 2001) were identified across the cp genomes and applied for multi-aspect studies in different plant taxa.…”
Section: Introductionmentioning
confidence: 99%